2022
DOI: 10.3390/ijerph191912447
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Short-Term Intervention with Lactobacillus salivarius Probiotic on Early Childhood Caries—An Open Label Randomized Controlled Trial

Abstract: ECC is a significant therapeutic and social problem and a global burden on public health. The aim of this clinical trial was to test whether a 2-week daily consumption of chewing tablets containing thermally inactivated L. salivarius reduces the 12-month caries increment compared to the control group. The investigation was a single-center, randomized, controlled open-label, blinded end-point evaluation trial in two parallel groups. At baseline, 140 generally healthy children between 3 and 6 years of age with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 62 publications
0
8
0
1
Order By: Relevance
“…As the amounts of these bacteria increased, so did the risk of caries. Other studies have also shown a link between these bacteria and the development of caries (1,48,49).…”
Section: Discussionmentioning
confidence: 90%
“…As the amounts of these bacteria increased, so did the risk of caries. Other studies have also shown a link between these bacteria and the development of caries (1,48,49).…”
Section: Discussionmentioning
confidence: 90%
“…Lee et al (2021) conducted a double-blind study indicating that oral probiotic tablets might contribute to reducing halitosis and improving quality of life related to oral health [34]. Staszczyk et al (2022) showed that consistent short-term probiotic consumption might slow dental caries onset in children [35]. Laleman et al (2019) reported that probiotic lozenges significantly reduced pocket depth in patients with periodontitis, particularly in deeper pockets [36].…”
Section: Resultsmentioning
confidence: 99%
“…Even though few studies have been performed to date, the findings show that probiotics are effective in preventing and treating oral infectious diseases, such as tooth decay, gingival problems, and bad breath. According to research, consuming probiotics reduces the S. mutans population in the body [ 18 ]. Few studies have been conducted to evaluate the outcomes of giving probiotic medicine locally.…”
Section: Discussionmentioning
confidence: 99%